2020
DOI: 10.3390/su12177130
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity Responses of the Macrophyte Algae Nitellopsis obtusa and Freshwater Crustacean Thamnocephalus platyurus to 12 Rare Earth Elements

Abstract: Due to unique chemical properties, rare earth elements (REEs) are increasingly used in versatile technological applications. They are considered emerging environmental contaminants, since they become mobile instead of being bound in rocks. At present, the information on REE effects to aquatic biota is scarce and contradictory. This study aims to explore the ecotoxicity of 11 lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Er, and Lu) and yttrium (Y) to charophyte algae Nitellopsis obtusa and microcrustaceans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This toxicity uniformity among the different REE could be explained by their similar physicochemical properties but there is no consensus in the literature. Some studies claim a higher toxicity of HREE compared to LREE (González et al, 2015;Manusadžianas et al, 2020) while Blaise et al (2018) found that LREE were more toxic than HREE. Dubé et al (2019) found a positive correlation between REE toxicity and electronegativity.…”
Section: Comparison Between the Different Reementioning
confidence: 99%
“…This toxicity uniformity among the different REE could be explained by their similar physicochemical properties but there is no consensus in the literature. Some studies claim a higher toxicity of HREE compared to LREE (González et al, 2015;Manusadžianas et al, 2020) while Blaise et al (2018) found that LREE were more toxic than HREE. Dubé et al (2019) found a positive correlation between REE toxicity and electronegativity.…”
Section: Comparison Between the Different Reementioning
confidence: 99%